2010
DOI: 10.1155/2010/102751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sacral Surface Therapeutic Electrical Stimulation on Early Recovery of Urinary Continence after Radical Retropubic Prostatectomy: A Pilot Study

Abstract: Objectives. To investigate whether sacral surface therapeutic electrical stimulation (SSTES) initiated during the early postoperative period would be effective towards early recovery of postprostatectomy urinary continence. Methods. A total of 35 consecutive patients who underwent radical prostatectomy by a single surgeon were enrolled in this study. Twenty early patients began pelvic floor muscle exercise (PME). Fifteen subsequent patients received SSTES postoperatively with no instruction for PME provided. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In additional to the traditional ES used above, a new type of ES called sacral surface therapeutic ES (SSTES) was developed by Nakagawa et al (2010), in which a specially designed plate electrodes were placed symmetrically on the skin surface over 2nd through 4th posterior sacral foramens. The effect of SSTES was significant, resulting the increase of maximum voided volume capacity and the decrease of urine loss in men after RP.…”
Section: Resultsmentioning
confidence: 99%
“…In additional to the traditional ES used above, a new type of ES called sacral surface therapeutic ES (SSTES) was developed by Nakagawa et al (2010), in which a specially designed plate electrodes were placed symmetrically on the skin surface over 2nd through 4th posterior sacral foramens. The effect of SSTES was significant, resulting the increase of maximum voided volume capacity and the decrease of urine loss in men after RP.…”
Section: Resultsmentioning
confidence: 99%
“…Sacral surface therapeutic electrical stimulation (SSTES) is a neuromodulation technique which has been used treat UI [18]. In RP patients, Nakagawa et al, reported that applying SSTES one day after surgery led to significantly larger mean void volume and significantly lower urine loss ratio as early as on day 3 as compared to control group which did not received any stimulation [24]. In another study, Morihiro et al, demonstrated that in laproscopic-RP patients application of SSTES combined with PFME showed higher continence percent as compared to only PFME group at 6 months (85%vs 57%) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study is not controlled as it lacks the placebo effect. One of the disadvantages of the neuromodulatory approach is the short carry-over effect [24]. Our current study lacks the evaluation of long term effect of the treatment regimen in maintaining continence for which follow up of the patients is required.…”
Section: Rpmentioning
confidence: 98%
See 1 more Smart Citation
“…Stimulation parameters were 50 Hz square wave with a 300 μs pulse width with output current of maximum tolerable intensity (26). The sites of electrode application were placed symmetrically on the skin surface over 2 nd through 4 th sacral outflow, where the lateral border of each electrode placed over the posterior superior iliac crest, and the inside border located one finger width from the midline (27).…”
Section: Subjectsmentioning
confidence: 99%